Pornography and erotism - González Montero, Sebastián Alejandro (Estudios de Filosofía, 2007)
This essay is born out of an intuition of Baudrillard according to which, in actuality, we attend a regime of image that imposes a certain way in which sexuality is related to the image of the body. In the plane of the image, the body is exhibited and, at the same time, a particular pretension to point to sex. Far from limiting itself to an intimate experience of desire, the image announces that sex has been detained in a symbolic relation that is characterized by the promise of the fetish, by the possibility of arousal and the compulsion to observe, the rest, as Baudrillard says, is literature. Well, in this essay both things are of equal interest to us. Through the concept of Erotism we try to perceive that which makes sexuality a radically internal experience; by means of the concept of Pornography we deal with the relation between the body, the image and sex. The first part dwells on the concept of Pornography as obscenity starting from the analysis done by Baudrillard in Seduction and in The Symbolic Exchange and Death. In the second part, we will try to show that the concept of Erotism can be understood as an interior experience and a conscience of the “betting on oneself”. The third part tries to put into play both concepts through the literary exercise of Miller and Jelinek with the goal of establishing the general frame of the problem of the delimitation between the Porno Image and Erotism as an interior experience. The final part is devoted to exposing some questions that arise of the contraposition from the concepts of Erotism and Pornography.